2021
DOI: 10.1073/pnas.2103513118
|View full text |Cite
|
Sign up to set email alerts
|

Identification of simple arylfluorosulfates as potent agents against resistant bacteria

Abstract: Sulfur fluoride exchange (SuFEx), a next generation of click chemistry, opens an avenue for drug discovery. We report here the discovery and structure–activity relationship studies of a series of arylfluorosulfates, synthesized via SuFEx, as antibacterial agents. Arylfluorosulfates 3, 81, and 101 showed potency to overcome multidrug resistance and were not susceptible to the generation of resistance. They exhibited rapid bactericidal potency and selectively killed gram-positive bacterial strains. These compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 65 publications
2
34
0
Order By: Relevance
“…Particularly, unique and appealing properties were often observed, which has attracted a fast-growing research interest on sulfonyl fluoride being a privileged warhead in chemical biology and drug discovery 1 , 4 , 18 , and successful examples keep emerging in the past years 18 27 . Remarkably, enhanced activity was often observed when the SO 2 F moiety was introduced, resembling, to some extent, the common beneficial effect of trifluoromethyl and fluorine groups in pharmaceuticals 18 20 , 28 33 . For example, Sharpless, and co-workers recently found that fluorosulfonylated Resveratrol showed a potent agent against resistant bacteria, higher than that of the parent compound by over 200-fold (Fig.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Particularly, unique and appealing properties were often observed, which has attracted a fast-growing research interest on sulfonyl fluoride being a privileged warhead in chemical biology and drug discovery 1 , 4 , 18 , and successful examples keep emerging in the past years 18 27 . Remarkably, enhanced activity was often observed when the SO 2 F moiety was introduced, resembling, to some extent, the common beneficial effect of trifluoromethyl and fluorine groups in pharmaceuticals 18 20 , 28 33 . For example, Sharpless, and co-workers recently found that fluorosulfonylated Resveratrol showed a potent agent against resistant bacteria, higher than that of the parent compound by over 200-fold (Fig.…”
Section: Introductionmentioning
confidence: 88%
“…For example, Sharpless, and co-workers recently found that fluorosulfonylated Resveratrol showed a potent agent against resistant bacteria, higher than that of the parent compound by over 200-fold (Fig. 1 ) 33 . Accordingly, novel and efficient synthetic protocols to broaden the scope of available sulfonyl fluorides are desirable 1 4 , 19 21 .…”
Section: Introductionmentioning
confidence: 99%
“…This result is inconsistent when compared with the findings of Hu and Coates (2021). It was hypothesized that this might be attributed to either difference in the strains, or there might be persistent bacteria that might have resulted in the regrowth of bacteria after 12 h (Zhang et al, 2021). Therefore, it is necessary to further investigate the causes for this weakened synergistic effect of mefloquine combination with colistin, after 12 h. This result also suggested that if the combinatorial treatment of mefloquine and colistin is used for clinical treatment of P. aeruginosa infection, the duration of administration might be shortened.…”
Section: Discussionmentioning
confidence: 72%
“…Since the introduction of SuFEx in 2014, various applications have been reported using this click chemistry [78][79][80][81][82][83][84][85][86][87][88][89][90]. Taunton et al performed a SAR study on a reported pyrimidine 3aminopyrazole scaffold and identified XO44 as a covalent probe suitable for kinome ABPP studies in live cells through covalent modification of lysine residues in ATP binding pockets (Figure 5B) HFIP carbamates KML-29 and ABX-1431; the latter analog is currently in clinical evaluation for treatment of neurological disorders.…”
Section: Trends In Pharmacological Sciencesmentioning
confidence: 99%